On the role of wind and tides in shaping the Gironde River plume (Bay of Biscay). (15th January 2023) - Toublanc, F.; Ayoub, N.K.; Marsaleix, P.
Abstract: We study the Gironde River plume in the Bay of Biscay (North-East Atlantic) using a high resolution modelling approach of the estuary-mouth-shelf continuum. The Gironde River plume flows over a gently sloping shelf where semi-diurnal tides reach an amplitude of 1.3–1.5 m on average; the Gironde River discharge undergoes a significant seasonal variability with floods (>1000 m 3 /s) in winter and spring. From two years of simulation (2011–12), we document the behavior of the plume under varying forcing conditions. We then discuss the dynamical mechanisms at play, from the estimate of some mechanical energy budget terms and using sensitivity runs: run with no tides, run with filtered atmospheric forcing (no variability at time scales smaller than 30 days) and run with no river runoff. We first show that the plume's properties are determined by the processes occurring in a transition area at the estuary outlet between the Royan and Cordouan sections. The outflow passes through a deep and narrow channel both because of bathymetric constraints and tides. Indeed, tides generate a residual circulation made of anticyclonic and cyclonic vortices with diameters of 5–12 km. Tides also induce intense mixing that strongly modifies the stratification between the two sections. The mean conditions lead to classify the plume as a narrow outflow which is a favorable condition for a bulge to be formed according to the literature. We indeed observe the recurrent formation of a bulge with sharp salinity gradients and a narrow coastal current. The bulge develops in moderate to high discharge conditions, during the spring to neap tides transition and when winds are weak. When the intensity of tides and wind increases, the bulge breaks down and the plume spreads offshore under upwelling wind conditions or along the coast (both in northward and southward directions) under strong eastward wind conditions. Tides are the main driver at the estuary outlet (with a bottom friction term larger by two orders of magnitude than over the adjacent shelf) but winds and atmospheric pressure are the main forcing over the inner shelf. These results evidence the need to model accurately the whole estuary-shelf continuum when studying the fate of riverine waters over the shelf. Highlights: An estuary-shelf continuum model is built to study the Gironde River plume dynamics. Tides play a key role at the mouth due to residual circulation and strong mixing. Bulge formed at spring to neap tides transition with low wind and significant runoff. The plume extends offshore or north to south along coast depending on wind direction. Tides and wind are the main drivers at the mouth and over the inner shelf respectively.